The salience of choice fuels independence: Implications for self-perception, cognition, and behavior - NANAKDEWA, Kevin (Institutional Knowledge at Singapore Management University, 2021)
More than ever before, people across the world are exposed to ideas of choice and have opportunities to make choices. What are the consequences of this rapidly expanding exposure to the ideas and practice of choice? The current research investigated an unexamined and potentially powerful consequence of this salience of choice: an awareness and experience of independence. Four studies (n = 1,288) across three cultural contexts known to differ in both the salience of choice and the cultural emphasis on independence (the United States, Singapore, and India) provided converging evidence of a link between the salience of choice and independence. Singaporean students who recalled choices rather than actions represented themselves as larger than their peers (study 1). Conceptually replicating this finding, study 2 found that Americans who recalled choices rather than actions rated themselves as physically stronger. In a word/nonword lexical decision task (study 3), Singaporean students who recalled choices rather than actions were quicker at identifying independence-related words, but not neutral or interdependence-related words. Americans, Singaporeans, and Indians all indicated that when working in an organization that emphasized choice, they would be more likely to express their opinions. Similarly, Americans, Singaporeans, and Indians reported a preference for working in such an organization (studies 4a and 4b). The findings suggest that the salience of personal choice may drive an awareness and experience of independence even in contexts where, unlike in the United States, independence has not been the predominant ethos. Choice may be an unmarked and proximate mechanism of cultural change and growing global individualism.